2001
DOI: 10.1017/s1049023x00025589
|View full text |Cite
|
Sign up to set email alerts
|

The Ice Storm in Eastern Canada 1998 KAMEDO-Report No. 74

Abstract: This is a report of the impact of the ice storm that struck eastern Canada on 04–09 January 1998. The storm deposited ice some 100 mm thick on the ground and on the electric power lines and eventually left 1.4 million households and much of the infrastructure without electrical power.Data were obtained through non-structured interviews of those involved. Most of the larger hospitals were equipped with emergency generating equipment and were able to provide most essential services. For most hospitals, non-emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Some, such as earlier bedtimes (Ghanem et al 2016;Heidenstrom and Kvarnlof, 2018;Mizuno and Okamoto-Mizuno, 2014) or heavier reliance on cars as opposed to public transport (Melnikov et al, 2015) have minimal health impacts. Others, such as attempting to remain at home without heating or siphoning petrol from cars to use in generators or elsewhere can lead to an increased number of deaths and injuries (Klein et al, 2007;Riddex and Dellgar, 2001).…”
Section: Changes In Daily Routinementioning
confidence: 99%
See 1 more Smart Citation
“…Some, such as earlier bedtimes (Ghanem et al 2016;Heidenstrom and Kvarnlof, 2018;Mizuno and Okamoto-Mizuno, 2014) or heavier reliance on cars as opposed to public transport (Melnikov et al, 2015) have minimal health impacts. Others, such as attempting to remain at home without heating or siphoning petrol from cars to use in generators or elsewhere can lead to an increased number of deaths and injuries (Klein et al, 2007;Riddex and Dellgar, 2001).…”
Section: Changes In Daily Routinementioning
confidence: 99%
“…Burger et al (2017) found that among Hispanic or Latino patients who were receiving healthcare before Hurricane Sandy, an increased number of days without power was associated with an increased likelihood of evacuating from the area. Riddex and Dellgar (2001) reported that between 25%-56% of people evacuated their homes depending on the region during the 1998 Canadian ice storm. Most sheltered with friends or family, but 140,000 had to spend one night or more in shelters (Riddex and Dellgar, 2001).…”
Section: Evacuationmentioning
confidence: 99%
“…Over 95% of the 322 868 km (200 000 miles) of the national electric power transmission cable is over ground (Abel 2009), and in the Midwest an even smaller fraction is buried (<1%). Under extreme ice accumulations the resulting loads (particularly when icing is associated with high winds) can lead to failure of support structures and interruption to electricity transmission (Riddex & Dellgar 2001, Jones et al 2004). An analysis of large-scale failures of the electricity distribution network over North America indicated 31.4% were associated with extreme wind or rain events, and 11% were attributable to ice accumulation (Hines et al 2009).…”
Section: Energymentioning
confidence: 99%
“…Little research has addressed disaster preparedness in agencies providing services to older and/or disabled clients in their homes. Almost all of this research has been limited to narrative reports about the impact of a disaster on clients of home care services, 25 narrative accounts of community-based initiatives, 26 responses of a single agency after a disaster, 27 or ways home healthcare nursing can better prepare to care for clients. 28 " 31 One recent descriptive account was based on a mailed survey of eight home care agencies located near the World Trade Center at the time of the 11 September 2001 terrorist attack.…”
Section: Previous Studies Of Preparedness Of Agencies Providing In-hmentioning
confidence: 99%